STUDY OF BIOCORROSION BEHAVIOUR OF AA5083 ALLOY BY THE BACTERIA SERRATIA RUBIDAEA STRAIN SKC-11 IN THE MARINE ENVIRONMENT - Alhadi, Afif
Indonesia, which is the largest archipelagic country in the world, has various advantages from its geographical location and resources. Because of that reason to facilitate inter-island connectivity and increase the utilization of maritime potential, it is necessary to develop the shipping industry. Ships that are a mode of sea transportation have a high risk to have a high risk of being corroded, especially in the hull section. Aluminum alloy 5083 (AA5083) is one of the aluminum alloys that can be used as a ship's hull because it has high corrosion resistance, lightweight, good workability, and can be recycled. However, in certain circumstances, aluminum can experience corrosion due to chloride ion attacks and microbiological Influenced Corrosion (MIC) phenomena. This research was conducted to determine the effect of the presence of sulfate-reducing bacteria (SRB) Serratia rubidaea strain SKC-11 on the biocorrosion process of aluminum alloy 5083 (AA5083) in seawater from Santolo Beach, West Java.